Wear analysis of Silicon Nitride (Si3N4) cutting tool in dry machining of T6061 Aluminium Alloy - Mohamed Ariff, Tasnim Firdaus; Shafie, Nurul Syamira; Mahamad Zahir, Zamzahariah (Trans Tech Publications Ltd., Switzerland, 2013)
Dry machining is an eco-friendly machining process and its importance in the manufacturing industries should be taken seriously. Machining without the use of any cutting fluid is becoming increasingly more popular due to concerns regarding the safety of the environment and reducing cost. Dry and wet turning of T6061 aluminium alloy was performed on a lathe by using Silicon Nitride (Si3N4) inserts as the cutting tool. Tool wear behaviour of Si3N4 cutting tool were studied with the aim of finding the optimum cutting conditions for both dry and wet machining. Machining was performed at four different cutting speeds; 292, 388, 518 and 689 m/min using two different cutting parameters (feed rate, f = 0.2 mm/rev, depth of cut, d = 0.1 mm and f = 0.4 mm/rev, d = 0.2 mm). Material removal rate (MRR) was also obtained and the temperature at the tool-chip interface were measured using an infrared (IR) thermometer as to see the effect of temperature rise during machining. Dry machining with smaller cutting parameters resulted in lower wear rates by 37 to 48% for all four cutting speeds. Nevertheless, reduction of wear rate by 38 to 57% was found from wet machining. The optimum cutting speed for both dry and wet machining of T6061 aluminium alloy using Si3N4 cutting tool was found to be 518 m/min for both cutting parameters. However, the optimum cutting parameters are apparently with the feed rate of 0.4 mm/rev and depth of cut of 0.2 mm. At the optimum cutting speed, the tool tip temperature for dry machining was higher than wet machining by 40 and 51% for f = 0.2 mm/rev and f = 0.4 mm/rev respectively. Dry machining of T6061 Aluminium alloy can be more suitable particularly at higher cutting speed with interrupted cutting operations.